Effects of Bio-Slurry and Chemical Fertiliser Application on Soil Physicochemical Properties and Selected Heavy Metal Concentrations in Maize and Brassica Vegetables in Malawi - Grace Thole Katola; Ephraim Vunain (Environmental Health Insights, 2026)
This study evaluated the effects of bio-slurry and chemical fertiliser application, relative to an unamended control, on soil physicochemical properties and the concentrations of selected heavy metals (Fe, Mn, Zn, Cu, Pb, Cd, Cr, and Hg) in soil and in maize ( Zea mays L. ), rape ( Brassica napus ), and Chinese cabbage ( Brassica pekinensis ) grown in Zomba, Malawi. A randomised complete block design with three treatments (100% bio-slurry, 100% chemical fertiliser, and an unamended control) and three replications was used. Soil samples were collected before planting and after harvest, and soil, bio-slurry, and crop samples were analysed for heavy metals by atomic absorption spectrometry. Bio-slurry significantly increased soil organic carbon, organic matter, and exchangeable bases (Ca, Na, Mg, K) relative to chemical fertiliser and the control, whereas chemical fertiliser and the control were both associated with a significant decline in soil pH. All measured heavy metal concentrations in soil and crops remained below FAO/WHO permissible limits, with iron (Fe) the most abundant and cadmium (Cd) the least abundant metal overall. However, the bio-slurry itself exceeded CODEX microbiological limits for mesophilic aerobic bacteria, moulds, and coliforms, indicating a microbiological food-safety concern that requires further treatment or hygienic handling before field application. The findings indicate that bio-slurry improves soil fertility more effectively than chemical fertiliser without increasing heavy-metal risk in the crops tested, but that its microbiological quality must be addressed before it can be recommended as an unqualified safe soil amendment in Malawi.